Fundamental of Entrepreneurship ENT300 : K.F.E.M Goat's / Kelvin Charles ... [et al.] - Charles, Kelvin; Jamin, Edward; Sebastian, Florrence; Assang, Mairen (2015)
After done with a lot of researches, interview and investigation, all of us have agreed to narrow our business on selling healthy goats. Lastly, we came up with a business plan of partnership and our company will be known as K.F.E.M Goat's. Our company provides the healthiest goats to the customers. In the process of launching this business plan, we need to take the five major business establishments into consideration which are management, administration, operation, marketing and finance. We have agreed that Kelvin anak Charles will be our General Manager and Administration Manager, Edward anak Jamin willebe our Marketing Manager, Florrence binti Sebastian Halis will be our Operation Manager, Mairen anak Assang will be our Financial Manager. The selection of General Manager is based on consensus among all the partnerships agree and based on the experiences, skill and ability.